Detection and sequencing of rotavirus among sudanese children - Magzoub, Magzoub Abbas (Pan Afr Med J, 2017)
INTRODUCTION: Diarrheal diseases are a big public health problem worldwide, particularly among developing countries. The current study was conducted to detect and characterize group A rotavirus among admitted children with gastroenteritis to the pediatric hospitals, Sudan. METHODS: A total of 755 stool samples were collected from Sudanese children with less than 5 years of age presenting with acute gastroenteritis during the period from April to September 2010. Enzyme-linked immunosorbent assay (ELISA) was used to Detection of Rotavirus antigens. Ribonucleic acid (RNAs) were extracted from rotavirus-positive stool samples using (QIAamp(®) Viral RNA Mini Kit). (Omniscript(®) Reverse Transcription kit) was used to convert RNA to complementary Deoxyribonucleic acid (cDNA). The cDNAs were used as template for detection of VP4-P (P for Protease-sensitive) and VP7-G (G for Glycoprotein) genotyping of Rotavirus using nested PCR and sequencing. RESULTS: Out of the 755 stool samples from children with acute gastroenteritis, 121 were positive for rotavirus A. Among 24 samples that were sequenced; the VP7 predominant G type was G1 (83.3%), followed by G9 (16.7%). Out of these samples, only one VP4 P[8] genotype was detected. CONCLUSION: As a conclusion the VP7 predominant G type was G1, followed by G9 whereas only one VP4 genotype was detected and showed similarity to P[8] GenBank strain. It appears that the recently approved rotavirus vaccines in Sudan are well matched to the rotavirus genotypes identified in this study, though more studies are needed.